ESTIMASI LIMPASAN PERMUKAAN DAS MIKRO BRANTAS HULU KECAMATAN BUMIAJI KOTA BATU MENGGUNAKAN PENGINDERAAN JAUH DAN SISTEM INFORMASI GEOGRAFIS - Muhammad Alimin; Kurniawan Sigit Wicaksono; S Sudarto (Jurnal Tanah dan Sumberdaya Lahan, 2015)
Land use changes are factors affecting the occurrence of surface runoff. By using Rational Method, the average yield calculation of surface runoff occurring on 7 February to 10 April 2015 ranged between 1.15 x 10-8 m3 sec-1 or 1.38 L m-2 and 3.75 x 10-8 m3 sec-1 or 2.37 L m-2. By using Chin-ong Meter Method, Â the yields of surface runoff occurring on 7 February to 10 April 2015 were 2.6 L m-2, 3.9 L m-2, 5.0 L m-2, 5.8 L m-2, 6.1 L m-2, and 8.3 L m-2, respectively, for forest land use, intensive agricultural land use with apple crops, intensive agricultural land use with orange crops, intensive agricultural land use with beans crops, intensive agricultural land use with ground peanut, and fallow land use. Results of paired t test between the results of Rational Method with Chin-ong Meter Method showed that there were no significant differences with a P-value table of 0.41 > Î± = 0.05. Area of mechanical and vegetative conservation priorities in Brantas Watershed Upstream Micro with very prone level of runoff were Bulukerto Village of 41.45 ha and Bumiaji Village of 30.74 ha.Â